Cocoa programming fundamentals livelessons - Chisnall, David (Addison-Wesley Professional, 2010)
"Cocoa Programming Fundamentals LiveLessons provides a video guided tour of the powerful and elegant Cocoa APIs and programming tools found on Mac OS X. Expert author and developer David Chisnall explains how Cocoa's core frameworks and components work, and then demonstrates how to put them to use in designing and developing sophisticated Mac OS X applications"--Resource description page.